2020
DOI: 10.1002/jcsm.12617
|View full text |Cite
|
Sign up to set email alerts
|

Muscle memory: myonuclear accretion, maintenance, morphology, and miRNA levels with training and detraining in adult mice

Abstract: Background In the context of mass regulation, 'muscle memory' can be defined as long-lasting cellular adaptations to hypertrophic exercise training that persist during detraining-induced atrophy and may facilitate future adaptation. The cellular basis of muscle memory is not clearly defined but may be related to myonuclear number and/or epigenetic changes within muscle fibres. Methods Utilizing progressive weighted wheel running (PoWeR), a novel murine exercise training model, we explored myonuclear dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(123 citation statements)
references
References 83 publications
4
111
0
1
Order By: Relevance
“…Acute RE also promotes a reorganization of rDNA methylation patterns along the repeat. The specific consequences and lasting effects of this acute epigenetic remodeling of rDNA deserve further investigation, but if persistent over time, could contribute to a previously observed epigenetic "epi-memory" of prior exercise exposure that facilitates future muscle adaptability (Sharples et al, 2016;Seaborne et al, 2018;Moberg et al, 2020;Murach et al, 2020;Snijders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute RE also promotes a reorganization of rDNA methylation patterns along the repeat. The specific consequences and lasting effects of this acute epigenetic remodeling of rDNA deserve further investigation, but if persistent over time, could contribute to a previously observed epigenetic "epi-memory" of prior exercise exposure that facilitates future muscle adaptability (Sharples et al, 2016;Seaborne et al, 2018;Moberg et al, 2020;Murach et al, 2020;Snijders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With these parallel approaches, we reveal novel information on genetic and epigenetic transcriptional control of the translational apparatus following exercise. Our findings may have implications for individual heterogeneity in exercise responsiveness to training (Ahtiainen et al, 2016;Sparks, 2017;Lavin et al, 2019), as well as the epigenetic mechanisms of potentiated exercise adaptability related to long-term cellular "muscle memory" (Murach et al, 2019;Murach et al, 2020;Snijders et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…As suggested by authors [ 237 ], the muscle memory of hypertrophic response may be independent of myonuclear number, and probably due to myonuclear DNA methylation, histone modifications, miRNA expression, and other epigenetic mechanisms. As underlined in the study of Murach et al [ 48 ], miR-1 downregulation after a resistance training program remains lower after six months of detraining and could contribute to make a kind of memory induced by a first training adaptation to facilitate regrowth during further exposure. Reinforcing the role of miRNAs in skeletal muscle mass maintenance, it was suggested that miR-21 expression in SCs and muscle could inhibit myogenesis in old mice and contribute to the decline in muscle regeneration during aging [ 238 ].…”
Section: Implication Of Satellite Cells and Myonuclear Accretionmentioning
confidence: 99%
“…Importantly, the involvement of satellite cells in skeletal muscle mass regulation has been recently questioned but new data highlighted their importance in myonuclear accretion and muscle remodeling during exercise training [ 48 , 49 , 50 ]. Finally, recent data underlined the importance of an epigenetic regulation (e.g., DNA and histone modifications, expression of specific microRNAs) of skeletal muscle mass, especially during resistance exercise [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transwomen, who have been exposed to higher circulating levels of testosterone during puberty than cisgender women, may have higher myonuclei per fibre values that are then retained for prolonged periods after the commencement of GAT (despite decrements in muscle mass) giving them a retained advantage that may be permanent [31]. Myonuclear permanence may also not be the predominant mechanism in the muscle memory phenomenon and that other mechanisms such as an epigenetic memory or residual miRNA levels may play a significant role [32,33].…”
Section: Introductionmentioning
confidence: 99%